An investigation of empirical properties of South African bonds - Mate, Janet (Department of Finance and Tax, 2017)
This study investigates empirical properties of South African bonds over the period 2000 to 2016. In particular, it investigates i) mean reversion in bond returns; ii) the correlation between bond returns and the inflation rate; and, iii) the correlation between bond returns and equity returns. An understanding of bond return dynamics would allow bond investors to assess which bond properties work in their favour. Thus this study seeks to guide bond investors, and to add to the knowledge of the bond market concerning bond return dynamics in an emerging market economy. The study employs a quantitative research methodology, using a nonexperimental research design. The investigation is carried out at the macroeconomic level using the JSE All Bond Indices as the bond investment proxy, the FTSE/JSE All Share Total Return Index as the equity investment proxy, and the Consumer Price Index as the proxy used to measure the inflation rate. The sample autocorrelation function is used to test for mean reversion and the Kendall Tau-b correlation test is used for the correlation investigations. This study does not find statistically significant evidence of long term mean reversion but finds statistically significant evidence of short-term mean reverting behaviour in the period 2013-2016. Furthermore, this study reveals that short-term serial correlations vary and are sensitive to political developments in the economy. The correlation analysis between bond returns and the inflation rate and bond returns and stock returns did not return statistically significant correlation values. However, further analysis provided evidence against the use of bonds as an inflation hedge and of diversification benefits to be reaped from combining bonds and stocks together in a portfolio.